IMPLEMENTASI SAINS TEKNOLOGI MASYARAKAT UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA FISIKA LINTAS MINAT - Mushthofa, Zayyinul; Yulianti, Dwi; Linuwih, Suharto (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
The Curriculum 2013 for Senior High School instructs the students to study certain subejcts beyond their interest; one of them is cross-interest physics subject. Social class that studies cross-interest physics subject is suggested to relate science to technology and its functions in the society. Beside, they must possess the good creativity for 21 century; the critical thinking. The purpose of the study was to determine the effect of the scientific technology approach of society (STS) in critical thinking skills. The type of research used is quasi experimental with non-equivalent control group design. The subjects in this study were class X IPS in SMA Teuku Umar Semarang with X IPS 1 as the experimental class with 17 students and the control class X IPS 2 with 16 students. The learning model used is Problem Based Learning on the Business and Energy material. The results of the N-Gain test showed an increase in critical thinking skills of 0.36% after the STM approach was implemented.